Attitudes and practices in the management of ADHD among healthcare professionals who responded to a European survey. (18th September 2013) - Fitzgerald, M.; McNicholas, F.
Abstract : Objectives: To examine attitudes and practices in the management of attention-deficit/hyperactivity disorder (ADHD) among health professionals across seven European countries. Methods: The web-based survey was developed by an international steering committee of ADHD experts and consisted of 64 multiple-choice questions relating to ADHD, covering the following topics: attitudes, diagnosis, referral, treatment and improving care. Health professionals working with ADHD were identified using a medical marketing database (Medical Marketing Service Inc., IL, USA) and invited via email to participate in the survey. No incentive was offered for participation and the survey was only available in English. Results: Over 22 000 emails and postal invitations were sent. One hundred and thirty-four (0.6%) health professionals completed the survey. Results highlighted significant differences by profession and country. In general, ADHD is considered a clinically important and valid disorder ( n = 111, 84%), with biological underpinnings ( n = 82, 62%), continuing into adulthood ( n = 123, 93%) and responsive to treatment. Respondents from France were less likely to be convinced about biological validity ( n = 4, 27%) and those from Italy and France were more likely to be concerned about the risk of underdiagnosis ( n = 9, 64% and n = 9, 60%, respectively). Psychologists were the specialty who most frequently reported not believing in the diagnostic validity of ADHD ( n = 4, 19%). One-third ( n = 25, 35%) of respondents recommended medical tests before prescribing medication, with differences emerging by country despite the lack of support for such routine assessments in the guidelines. Conclusions: Despite the very low response rate, intriguing country- and profession-specific differences emerged in this study and warrant further exploration.